Consumer credit with over-optimistic borrowers - Florian Exler; Igor Livshits; James MacGee; Michele Tertilt (Bank of Canada, 2020)
There is active debate over whether borrowers' cognitive biases create a need for regulation to limit the misuse of credit. To tackle this question, we incorporate overoptimistic borrowers into an incomplete markets model with consumer bankruptcy. Lenders price loans, forming beliefs - type scores - about borrowers' types. Since over-optimistic borrowers face worse income risk but incorrectly believe they are rational, both types behave identically. This gives rise to a tractable theory of type scoring as lenders cannot screen borrower types. Since rationals default less often, the partial pooling of borrowers generates cross-subsidization whereby over-optimists face lower than actuarially fair interest rates. Over-optimists make financial mistakes: they borrow too much and default too late. We calibrate the model to the US and quantitatively evaluate several policies to address these frictions: reducing the cost of default, increasing borrowing costs, imposing debt limits, and providing financial literacy education. While some policies lower debt and filings, they do not reduce overborrowing. Financial literacy education can eliminate financial mistakes, but it also reduces behavioral borrowers' welfare by ending cross-subsidization. Score-dependent borrowing limits can reduce financial mistakes but lower welfare.
Keywords: E21; E49; G18; K35; 330; Credit and credit aggregates; Credit risk management; Financial system regulation and policies